2023
DOI: 10.3390/ijerph20042772
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 Diabetes and the Menstrual Cycle: Where/How Does Exercise Fit in?

Abstract: Regular exercise is associated with substantial health benefits for individuals with type 1 diabetes (T1D). However, the fear of hypoglycemia (low blood glucose) due to activity-induced declines in blood glucose levels acts as a major barrier to partaking in exercise in this population. For females with T1D, hormonal fluctuations during the menstrual cycle and their effects on blood glucose levels can act as an additional barrier. The impact that these cyclic changes may have on blood glucose and insulin needs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 93 publications
0
3
0
Order By: Relevance
“…who studied a group of Indian children and adolescents [ 49 ]. Ovarian function appears to be modified in adolescents with T1DM [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…who studied a group of Indian children and adolescents [ 49 ]. Ovarian function appears to be modified in adolescents with T1DM [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Women diagnosed with type 1 diabetes mellitus (T1DM) undergo fluctuations in their glycemic changeability due to variations in insulin receptor binding and affinity that are specifically linked to their menstrual cycle leading to Catamenial Hyperglycemia (10)(11)(12). Many studies has shown that compared to the early follicular phase, there is a higher likelihood of experiencing hyperglycemia during the periovulatory and early luteal phases.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of AOA is increased in PCOS together with some organ and non-organ-specific auto-antibodies [13]. Additionally, a link between PCOS, autoimmune oophoritis, and premature ovarian failure (POF) has been established [14,15]. Tubal sub-fertility contributes to 10%-30% of female causes of infertility.…”
Section: Introductionmentioning
confidence: 99%